Geochemical signatures of intense episodic anaerobic oxidation of methane in near-surface sediments of a recently discovered cold seep (Kveithola trough, NW Barents Sea) - M. Bazzaro; N. Ogrinc; F. Relitti; R. G. Lucchi; M. Giani; G. Adami; E. Pavoni; C. De Vittor (Marine Geology, 2020)
At cold seep environments, the detection of large 34S enrichments within bulk sulphide minerals has been frequently used as a proxy to infer the vertical migrations of the sulphate-methane transition zone (SMTZ). Processes related to the oxidative part of the sulphur cycle can alter the original stable sulphur isotope composition (δ34S) of the solid sulphur phases, in particular at the sediment-water interface. Identification of paleo and present positions of methane fronts in the sedimentary records requires the use of multiple geochemical proxies. Authigenic enrichment of Mo has been demonstrated to represent a valid and durable tracer of the past SMTZ depth fluctuations and of the intensities of the related methane seepages. This study is based on two closely-spaced short cores collected from the Main Drift of the Kveithola trough, a glacially-carved depression located in northwestern Barents Sea. Active fluid seepage has been recently reported in this area and a gas flare was specifically observed in proximity of the sampling sites where the cores object of our study were retrieved. In order to collect evidences of the possible occurrence of anaerobic oxidation of methane (AOM) at the sedimentwater interface of the investigated area and infer the entity of the associated methane flux, we combined the analyses of reduced sulphur species δ34S, total organic carbon and redox-sensitive elements. The negative δ34S values within the extracted solid sulphur phases (up to −49.1‰ for pyritic sulphur) show that organoclastic sulphate reduction (OSR) coupled with disproportionation of sulphur intermediates are the only active processes in the near-surface sediments. However, moderate to strong enrichments of Mo detected in the relatively organic carbon poor intervals of both cores and the lack of concurrent enrichments of Co, Cu, Ni, V and Zn, usually associated to OSR-dominated environment, suggested that the sulphidic conditions favouring the Mo enrichments were produced by AOM. Therefore, we infer that high methane ...